2021
DOI: 10.3390/bs11060083
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Psychotherapy Use, Male Role Norms, and Male-Typical Depression Symptoms: Examining 716 Men and Women Experiencing Psychological Distress

Abstract: Men as compared to women are half as often affected by depressive and anxiety disorders and seek significantly less help for mental health issues than women. Adherence to traditional male role norms (AtTMRN) may hinder men from describing prototypical depression symptoms and from seeking psychotherapy. The current study compared whether AtTMRN, gender role identity, or the experience of prototypical or male-typical externalizing mental health symptoms were associated with psychotherapy use in men and women. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 68 publications
(101 reference statements)
7
31
0
1
Order By: Relevance
“…With regard to psychotherapy use, male students showed a significantly lower current psychotherapy use and also a lower intention to use psychotherapy in the near future as compared to female students (see Table 1, Figure 2), which further corroborates previous reports from Germany or Switzerland [14][15][16]. However, when investigating gender differences in psychotherapy use by syndrome, only for the category any syndrome a significant difference was initially detected, which did not remain significant after correction for multiple testing.…”
Section: Integration Of Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…With regard to psychotherapy use, male students showed a significantly lower current psychotherapy use and also a lower intention to use psychotherapy in the near future as compared to female students (see Table 1, Figure 2), which further corroborates previous reports from Germany or Switzerland [14][15][16]. However, when investigating gender differences in psychotherapy use by syndrome, only for the category any syndrome a significant difference was initially detected, which did not remain significant after correction for multiple testing.…”
Section: Integration Of Findingssupporting
confidence: 89%
“…Furthermore, men show up to four-fold increased suicide rates and appear to be particularly vulnerable to commit suicide when facing economic or social losses [ 9 , 10 ]. This is in line with reports suggesting that overall men and women experience similar levels of psychological distress and mental disorders [ 11 ], yet men use psychotherapy about 30% less than women [ 12 , 13 , 14 , 15 , 16 ]. Whether this pattern differs with regard to differing psychological syndromes is, however, insufficiently studied.…”
Section: Introductionsupporting
confidence: 91%
“…[12] Approximately 69% of IMC patients are female [2], which makes it more likely for referrals from the clinic to be female due to this gender difference. Our results are also in line with previous literature that shows women seek psychological help more often than men and men tend to wait until they are experiencing high symptom burden [15]. HP referrals were more likely to be younger and less likely to be retired compared to non-referrals, which makes sense considering that age and employment status are likely correlated.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, men with strong GRC due to the restriction of their emotions were found to be less likely to address the topic of sexual health during patient–physician conversations (Komlenac et al, 2019). Lastly, men who strongly identified themselves with traits traditionally seen as masculine (measured with the Bem Sex Role Inventory; Bem, 1974) were found to be less likely to use psychotherapy when experiencing psychological distress (Eggenberger, Fordschmid, et al, 2021).…”
Section: Tmimentioning
confidence: 99%
“…For example, O’Neil’s (2008) review of over 230 studies demonstrated consistent associations between the experience of GRC and increased depression symptoms among men. And while depressive disorders have affected over 100 million men in the year 2019 (Global Burden of Disease Collaborative Network, 2021) and are still one of the strongest predictors for suicide among men (Yoshimasu et al, 2008), men who experience depression use psychotherapy significantly less often than do women (Eggenberger, Fordschmid, et al, 2021; Rommel et al, 2018; Roxo et al, 2021; Walther & Seidler, 2020).…”
Section: Tmimentioning
confidence: 99%